KARAKTERISTIK PENDERITA MALARIA DI WILAYAH KERJA PUSKESMAS SAMBAU KECAMATAN NONGSA KOTA BATAM TAHUN 2012 - Chrisnina Novelina; Hiswani .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Malaria is a disease caused by parasites of the genus Plasmodium that transmitted through the intermediary of a bite Anopheles spp. API Indonesia during the year 2012 amounted to 1,69/1.000. Malaria is still an endemic disease in the Batam City. Nongsa sub-district is one of the districts where malaria is endemic, where the malaria morbidity rate is still quite high at API in 2012 was 1,65/1.000. The research was done as descriptive study by using case series design, to determine the characteristics of malaria patients in work area Health Center of Sambau District Nongsa Batam City in 2012. Population was all patients with malaria was recorded in Health Centers of Sambau totalling 113 people. Sample is the total population. Data were statistically analyzed using Chi Square test. The highest proportion of malaria patients in the age group 25-32 years (23,0%), Male (57,5%), fisherman (26,5%), and 65,5% place in Sambau village. The highest type of diagnosis is positive malaria (58,4%) and cause of malaria is Plasmodium vivax (43,1%). There was no significant difference between gender based on cause of malaria (p= 0,793). For community, malaria control can be done by using mosquito repellent, clean up mosquito breeding nests, and preserve larva-eating fish, such as tilapia and head tin fish, and use mosquito nets during sleep to avoid mosquito bites.